The Development of Students Worksheets Based on Local Wisdom in Substances and Their Characteristics - Hairida Hairida; Vidya Setyaningrum (Universitas Negeri Makassar, 2020)
This study aimed to develop Student Worksheets (LKPD) based on the local wisdom of matter substances and their characteristics in order to improve the character of junior high school students. The development research design used was the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The instruments used in the study were validation sheets, observation sheets, response questionnaires, and self-assessment questionnaires about characters. The results of the study concluded that LKPD based on local wisdom was appropriate to be used in science learning, included in the practical category so as to make it easier for students to learn, and effectively develop students' character.